Ecolabelling: a meta-analytic structural equation modelling approach - Vinoi, Nivin; Vishwakarma, Pankaj (Marketing intelligence & planning, 2024)
PurposeResearchers have devoted considerable attention to ecolabel products and their purchase intention. However, empirical research often presents relatively unpredictable and uneven results. Thus, the relationship between the antecedents and outcome variables among ecolabelling studies, such as purchase intention, remains ambiguous. To address this gap in the literature, this study combines the Theory of Planned Behaviour (TPB) and Stimulus, Organism, Response (SOR) theory within a meta-analytic framework, consolidating existing literature on the purchase intention of eco-labelled products to analyse concrete relationships between antecedents and purchase intention.Design/methodology/approachWe conducted a comprehensive analysis of 37 studies and a total sample size of 16,672 participants. The analysis employed a MASEM technique, and the findings of the analysis offer empirical support for the significance of all the proposed relationships within the provided conceptual framework.FindingsThe results revealed that environmental advertising significantly impacts green attitude and later substantially influences consumers' intention to make environmentally conscious purchases. The present study also has examined the potential inclusion of different recommended moderators, such as time period and sample size.Research limitations/implicationsThe current study focuses on core variables consistently utilized in previous research. Apart from these, additional variables have also been considered in the ecolabelling literature but have not been included in the scope of this study. Future research endeavours may incorporate additional moderators, such as cultural differences and gender dominance, to further enhance the understanding of the subject matter.Originality/valueNotably, it stands out as one of the initial meta-analyses on ecolabelling, which also incorporated the examination of several moderators.